On the Perceptual Edge of Autonomy: The Problematics of Expressing the Needs of Others - Basson, Steve (Routledge, 1999)
This paper addresses the problematic conditions of perception that invest our interpretations of the built environment and capacity to fully express the desires of those we design for. Particular to this, is the manner by which we interpret an appropriate differentiated patterns of meaning from our readings of art, architecture and urban space, which represents the divergent range of social, cultural and institutional conditioning that informs the perceptions of each individual.